Supramolecular P4VP-pentadecylphenol naphthatenebisimide comb-polymer: mesoscopic organization and charge transport properties - Narayan, Rekha; Kumar, Prashant; Narayan, K. S.; Asha, S. K. (Journal of Materials Chemistry C, 2014)
A supramolecular comb polymer of pentadecyl phenol (PDP) substituted naphthalenebisimide (PDP-UNBI) with poly(4-vinylpyridine) (P4VP) is reported. The mesoscopic organization within the P4VP(PDP-UNBI), complexes was studied using wide-angle X-ray diffraction (WXRD) technicjues. The packing diagram obtained from the single-crystal XRD analysis of the PDP-UNBI crystals gave a clear picture of the initial arrangement present in self-associated PDP-UNBI alone. Correlating this with the XRD data of the hydrogen-bonded polymer complex provided insight into the probable packing of the P4VP chains within the crystalline lattice of PDP-UNBI leading to a highly ordered lamellar packing. Transmission electron microscopy (TEM) revealed the uniform mesomorphic lamellar structures in the domain range of similar to 5-10 nm. Furthermore, the charge carrier mobility measurements observed from space-charge-limited current (SCLC) measurements demonstrated that transport behaviour of the hydrogen-bonded P4VP(PDP-UNBI) complex (2 x 10(-2) cm(2) V-1 s(-1)) was comparable to that of the crystalline naphthalenebisimide molecule itself (9 x 10(-3) cm(2) V-1 s(-1)), which is a great achievement, since the complex now offers a package of solution-processable n-type semiconductor polymer with mobility equivalent to that of a small crystalline molecule.

Sustainable bioprocess technology for producing food-flavour (+)-γ-decalactone from castor oil-derived ricinoleic acid using enzymatic activity of Candida parapsilosis: Scale-up optimization and purification using novel composite - Syed, Naziya; Singh, Suman; Chaturvedi, Shivani; Kumar, Prashant; Kumar, Deepak; Jain, Abhinav; Sharma, Praveen Kumar; Nannaware, Ashween Deepak; Chanotiya, Chandan Singh; Bhambure, Rahul; Kumar, Pankaj; Kalra, Alok; et al. (Journal of Biotechnology, 2024)
Ricinoleic acid (RA) from castor oil was employed in biotransformation of peach-flavoured gamma-decalactone (GDL), using a Candida parapsilosis strain (MTCC13027) which was isolated from waste of pineapple crown base. Using four variables-pH, cell density, amount of RA, and temperature-the biotransformation parameters were optimized using RSM and BBD. Under optimized conditions (pH 6, 10 % of microbial cells, 10 g/L RA at 28 degrees C), the conversion was maximum and resulted to 80 % (+)-GDL (4.4 g/L/120 h) yield in shake flask (500 mL). Furthermore, optimization was achieved by adjusting the aeration and agitation parameters in a 3 L bioreactor, which were then replicated in a 10 L bioreactor to accurately determine the amount of (+)-GDL. In bioreactor condition, 4.7 g/L (>85 %) of (+)-GDL is produced with 20 % and 40 % dissolved oxygen (1.0 vvm) at 150 rpm in 72 h and 66 h, respectively. Further, a new Al-Mg-Ca-Si composite column-chromatography method is developed to purify enantiospecific (+)-GDL (99.9 %). This (+)-GDL is 100 % nature-identical as validated through 14C-radio-carbon dating. Thorough chemical investigation of enantiospecific (+)-GDL is authenticated for its use as flavour. This bioflavour has been developed through a cost-effective biotechnological process in response to the demand from the food industry on commercial scale.
Keywords: (+)-gamma-Decalactone; Al-Mg-Ca-Si composite; Bioflavour; Candida parapsilosis; castor oil; Food-waste